The quality of compliance: investigating fishers' responses towards regulation and authorities. Issue 4 (1st December 2016) - Boonstra, Wiebren J; Birnbaum, Simon; Björkvik, Emma
Abstract: A substantial amount of scientific effort goes into understanding and measuring compliance in fisheries. Understanding why, how and when fishers follow or violate rules is crucial for designing effective fishery policies that can halt overfishing. Non‐compliance was initially explained almost exclusively with reference to economic and self‐interested motivations. More recently, however, most explanations involve a combination of economic, social, political and environmental factors. Despite this recent development towards more holistic explanations, many scientists continue to frame the issue in binary terms: fishers either follow rules, or they don't. In this article we challenge this binary interpretation and focus attention on the diversity of fishers' dispositions and perceptions that underpin compliant behaviour. To this aim we construct a typology of fishers' responses towards regulation and authorities, thereby developing conceptual tools to understand different motivations and attitudes that underlie compliance outcomes. For this purpose, we identify the motivational postures of 'creativity' and 'reluctance', and then highlight their empirical relevance with an interview study of Swedish fishers. Reasons for studying the quality and diversity of fishers' motivations and responses are not purely academic. Conceptualizing and observing the quality of compliance can help policymakers and managers gauge and anticipate the potentiality of non‐compliant fishing practices that may threaten the resilience of marine ecosystems.